Using the Theory of Plan Behavior and Norm Activation Model to Understand Individual Energy Conservation Behavior in Karachi, Pakistan: Using the Theory of Plan Behavior and Norm Activation Model to Understand Individual Energy Conservation Behavior in Karachi, Pakistan - Rasool, Faiz; Zuberi, Nabeel A.; Siddiqui, Naila Usman; Madni, Munazza (International Journal of Economic and Environmental Geology, 2019)
The environmental problems are considered as a serious threat to the future of humanity. The adoption of sustainable behaviors is considered a necessary step to deal with the environmental challenges. Energy conservation behavior is an environment friendly behavior that has been promoted in many societies. Researchers have been studying the determinants of energy conservation behavior for many years, in western countries. However, energy conservation behavior of individuals in the house has not received attention of researchers in Pakistan. In this study, theory of planned behavior and norm activation model are used to study energy conservation behavior of 1250 college and university students in Karachi. Our results show that attitudes, subjective norms, awareness of consequences, ascription of responsibility and personal norm, all have a positive relation with energy conservation behavior. Socio-demographic variables had no statistically significant relation with energy conservation. It is believed that electronic and social media and religious scholars can play a key role in raising awareness of environmental issues and encouraging the adoption of environment friendly behaviors in Pakistan.